2018
DOI: 10.1016/j.hrtlng.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Stress, cognitive appraisal, coping, and event free survival in patients with heart failure

Abstract: The cognitive appraisal of the stressors related to HF may lead to negative coping strategies that are associated with worse event-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 60 publications
(61 reference statements)
1
21
0
1
Order By: Relevance
“…Findings showed that primary cognitive evaluation had a significant negative effect on problemoriented coping style and positively significant effect on emotion-oriented and avoidance styles and secondary cognitive evaluation had a significant positive effect on problem-oriented coping style and significantly negative effect on emotion-oriented and avoidance styles. These findings were consistent with the findings of Kang, et al (2018), Alhurani, et al (2018), Hermsen, et al (2016, Goodarzi, et al (2015) and Shokri, et al (2014). For example, Kang, et al (2018) showed that the primary evaluation had a significant negative effect on problem-oriented style and a significant positive effect on emotion-oriented style, and the secondary evaluation had a significant positive effect on problem-oriented style and a significant negative effect on emotion-oriented style.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings showed that primary cognitive evaluation had a significant negative effect on problemoriented coping style and positively significant effect on emotion-oriented and avoidance styles and secondary cognitive evaluation had a significant positive effect on problem-oriented coping style and significantly negative effect on emotion-oriented and avoidance styles. These findings were consistent with the findings of Kang, et al (2018), Alhurani, et al (2018), Hermsen, et al (2016, Goodarzi, et al (2015) and Shokri, et al (2014). For example, Kang, et al (2018) showed that the primary evaluation had a significant negative effect on problem-oriented style and a significant positive effect on emotion-oriented style, and the secondary evaluation had a significant positive effect on problem-oriented style and a significant negative effect on emotion-oriented style.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the results of Kang et al (2018) showed that the initial evaluation had a significant negative effect on problem-oriented style and a significant positive effect on emotion-oriented style, and the secondary evaluation had a significant positive effect on problemoriented style and a significant negative effect on emotion-oriented style. Alhurani, et al (2018) concluded that primary cognitive evaluation had a significant negative relationship with problem-oriented style and positively significant relationship with emotion-oriented style and secondary cognitive evaluation had a significant positive relationship with problem-oriented style and negatively significant relationship with emotion-oriented style. In another study, Hermsen, et al (2016) reported that the primary assessment had a significant negative relationship with problem-oriented style, a positively positive relationship with emotion-oriented style, and the secondary assessment had a significant positive relationship with problemoriented style and a significant negative relationship with emotion-oriented style.…”
Section: Introductionmentioning
confidence: 98%
“…We found that individuals with higher perceived stress levels are more likely to have anxiety symptoms and cognitive reappraisal may buffer this impact. Our study demonstrates that perceived stress and cognitive reappraisal act collectively to influence anxiety symptoms, whereas others have found cognitive appraisal has been shown to determine the impact of stress response ( 51 ). Cognitive appraisal refers to the estimation of the stress event itself, while cognitive reappraisal is an individual’s selective interpretation of the meaning of the stress event ( 52 ).…”
Section: Discussionmentioning
confidence: 47%
“…Having that only the NGSs with less stress than nurses in the second and third rotation is a surprising result. It is expected that nurses with less experience show a higher stress level than nurses with more experience ( Alhurani et al., 2018 ). The explanation for this result could be attributed to the perception of the NGNs as fresh graduates with less responsibility on them.…”
Section: Discussionmentioning
confidence: 99%